ICES Operational Oceanographic Products and Services - Gridded Copepod abundance data ... - Flanders Marine Institute VLIZ, Belgium; Royal Netherlands Institute For Sea Research NIOZ, Netherlands (Marine Data Archive, 2018)
The International Council for the Exploration of the Sea (ICES), located in Copenhagen is an organisation providing scientific advice in the North Atlantic on the exploitation and stewardship of the marine ecosystem and marine living resources. Within this role, it is developing an integrated ecosystem advice at a regional level which will be appropriate to managers, policy developers and interested stakeholders. As part of this ICES has recently constructed “Ecosystem Overviews” which describe the trends in pressures and state of regional ecosystems. These advice processes require regular inputs of monitoring information on the oceanography and hydrology of the regions, called Operational Oceanographic Products and Services (OOPS). ... : This dataset consists of gridded abundance map of copepod species. This product was developed with DIVA (Data-Interpolating Variational Analysis). Data was provided by SAHFOS (Continuous Plankton Recorder (CPR) data (zooplankton) from the Sir Alister Hardy Foundation for Ocean Science (SAHFOS).). ...